Listening to the voices of teachers (2014)
This article is the product of the research “Beliefs of a Group of Thirteen Teachers about the Labour Conditions that Dignify or Make their Profession Precarious”, which intends to make known the teacher’s beliefs through their own voice, using Grounded Theory as a research method, techniques like semi structured interview, autobiographic narrative and a focal group to collect information. From the data obtained an analysis is built in which lets us know the teacher’s feelings towards the job they perform, and finally, to contribute the design of a proposal of human development to help raise the profile of the profession.